2020
DOI: 10.1002/sim.8754
|View full text |Cite
|
Sign up to set email alerts
|

A pilot design for observational studies: Using abundant data thoughtfully

Abstract: Observational studies often benefit from an abundance of observational units. This can lead to studies that—while challenged by issues of internal validity—have inferences derived from sample sizes substantially larger than randomized controlled trials. But is the information provided by an observational unit best used in the analysis phase? We propose the use of a “pilot design,” in which observations are expended in the design phase of the study, and the posttreatment information from these observations is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…The auto_stratify function in stratamatch divides subjects into strata using a prognostic score (see Hansen (2008)), which summarizes the baseline variation most important to the outcome. In addition to producing strata of more regular size and composition, balancing treatment and control groups based on the prognostic score may confer several statistical benefits: increasing precision (Aikens et al, 2020;Leacy and Stuart, 2014), providing some protection against mis-specification of the propensity score (Leacy and Stuart, 2014;Antonelli et al, 2018), and decreasing the susceptibility of an observed effect to being explained away by unobserved confounding (Rosenbaum and Rubin, 1983;Aikens et al, 2020). However, fitting the prognostic score on the same data set raises concerns of overfitting and may lead to biased effect estimates (Hansen, 2008;Abadie et al, 2018).…”
Section: A Prognostic Score Stratification Pilot Designmentioning
confidence: 99%
See 4 more Smart Citations
“…The auto_stratify function in stratamatch divides subjects into strata using a prognostic score (see Hansen (2008)), which summarizes the baseline variation most important to the outcome. In addition to producing strata of more regular size and composition, balancing treatment and control groups based on the prognostic score may confer several statistical benefits: increasing precision (Aikens et al, 2020;Leacy and Stuart, 2014), providing some protection against mis-specification of the propensity score (Leacy and Stuart, 2014;Antonelli et al, 2018), and decreasing the susceptibility of an observed effect to being explained away by unobserved confounding (Rosenbaum and Rubin, 1983;Aikens et al, 2020). However, fitting the prognostic score on the same data set raises concerns of overfitting and may lead to biased effect estimates (Hansen, 2008;Abadie et al, 2018).…”
Section: A Prognostic Score Stratification Pilot Designmentioning
confidence: 99%
“…However, fitting the prognostic score on the same data set raises concerns of overfitting and may lead to biased effect estimates (Hansen, 2008;Abadie et al, 2018). For this reason, (Aikens et al, 2020) suggest using a pilot design for estimating the prognostic score.…”
Section: A Prognostic Score Stratification Pilot Designmentioning
confidence: 99%
See 3 more Smart Citations